Biological and Oxidative Effect of Ellagic Acid on Saccharomyces cerevisiae: A New Way for Culture Developing - Gok, Ozlem; Beyaz, Seda; Aslan, Abdullah (Inst Tecnologia Parana, 2021)
In this study, the effects of Ellagic acid ( EA) on protein expression in yeasts and cellular development were investigated. Four groups were formed. Groups: 1) Control group; yeast only cultivated group; 2) Ellagic Acid (EA) group: EA (10%) given group; 3) Hydrogen peroxide (H2O2) Group: The group given H2O2 (15 mM); 4) EA + H2O2 group: EA (10%) + H2O2 (15 mM) group. After sterilization, EA (10%) and H2O2 (15 mM) were added to the Saccharomyces cerevisiae (S. cerevisiae) cultures and the cultures were grown at 30 degrees C for 1 hour, 3 hours, 5 hours and 24 hours (overnight). S. cerevisiae cell growth, lipid peroxidation MDA (malondialdehyde) analysis and GSH (glutathione) level were analyzed by spectrophotometer. Total protein changes were determined by SDS-PAGE electrophoresis and measured by the Bradford method. According to the obtained results, compared with the H2O2 group, cell development (1, 3, 5 and 24 hours), GSH level and total protein synthesis (24 hours) were increased with EA, while MDA level (24 hours) decreased. These results show that EA reduces oxidative damage, increases cell growth and it has a protective effect to promote protein synthesis in S. cerevisiae culture.
Keywords: Ellagic acid; H2O2; Saccharomyces cerevisiae; SDS-PAGE